Dihydroceramides: their emerging physiological roles and functions in cancer and metabolic diseases - Lachkar, Floriane; Ferré, Pascal; Foufelle, Fabienne; Papaioannou, Alexandra (American journal of physiology: endocrinology and metabolism, 2021)
Dihydroceramides (DhCers) are a type of sphingolipids that for a long time were regarded as biologically inactive. They are metabolic intermediates of the de novo sphingolipid synthesis pathway, and are converted into ceramides (Cers) with the addition of a double bond. Ceramides are abundant in tissues and have well-established biological functions. On the contrary, dihydroceramides are less prevalent, and despite their hitherto characterization as inert lipids, studies of the past decade began to unravel their implication in various biological processes distinct from those involving ceramides. These processes include cellular stress responses and autophagy, cell growth, pro-death or pro-survival pathways, hypoxia, and immune responses. In addition, their plasma concentration has been related to metabolic diseases and shown as a long-term predictor of type 2 diabetes onset. They are thus important players and potential biomarkers in pathologies ranging from diabetes to cancer and neurodegenerative diseases. The purpose of this mini-review is to highlight the emergence of dihydroceramides as a new class of bioactive sphingolipids by reporting recent advances on their biological characterization and pathological implications, focusing on cancer and metabolic diseases.